Risk factors for atrial fibrillation in dogs with dilated cardiomyopathy - Guglielmini, Carlo; Valente, Carlotta; Romito, Giovanni; Mazzoldi, Chiara; Baron Toaldo, Marco; Goncalves Sousa, Marlos; Wolf, Marcela; Beluque, Tamyris; Domenech, Oriol; Patata, Valentina; Porciello, Francesco; Ferrari, Paolo; et al. (Frontiers in Veterinary Science, 2023)
Atrial fibrillation secondary to dilated cardiomyopathy frequently affects large breed dogs. This multicenter retrospective study aimed to identify the risk factors of developing atrial fibrillation in dogs with dilated cardiomyopathy. We included 89 client-owned dogs with occult and overt echocardiographic dilated cardiomyopathy. Of these, 39 dogs (44%) had atrial fibrillation, 29 dogs (32.6%) maintained a sinus rhythm, and 21 dogs (23.6%) showed other cardiac arrhythmias. Comparison of clinical and echocardiographic variables between dogs developing atrial fibrillation and those not developing atrial fibrillation was carried out and ability to distinguish between these two groups of dogs was evaluated by receiver operating characteristic curve analysis. Univariate and multivariable logistic regression analysis estimated the odds ratio (OR) with 95% confidence interval (CI) of developing atrial fibrillation. Left atrial diameter had high accuracy (area under the curve = 0.816, 95% CI = 0.719-0.890) to predict development of atrial fibrillation at the cut-off of >4.66 cm. After multivariable stepwise logistic regression analysis, only increased left atrial diameter (OR = 3.58, 95% CI = 1.87-6.87; P < 0.001) and presence of right atrial enlargement (OR = 4.02, 95% CI = 1.35-11.97; P = 0.013) were significant predictors of atrial fibrillation development. Atrial fibrillation is a common complication of dilated cardiomyopathy in the dog and is significantly associated with increased absolute left atrial diameter and right atrial enlargement.